From 65 to 70 years old: what is the best approach in the treatment of glioblastoma? - Ulrich, João; Delgado, Diogo; Figueiredo, André; Simas, Miguel; Neves, Maria Eduarda; Pisco, Joana; Silva, Manuel Carmo da; Branquinho, André Abrunhosa; Amado, Ana; Pina, Maria Filomena de (International Journal of Advances in Medicine, 2021)
Background: Glioblastoma (GBM) is the most common primary CNS tumor in adults. Between 65-70 years of age, treatment involves the best possible surgical removal followed by radiotherapy (RT), with or without temozolomide (TMZ). After assessing whether patients can tolerate TMZ, doubts regarding RT regimens persist in this age group. This study aimed to compare the overall survival (OS) in GBM patients aged 65-70 years, in two RT regimens with TMZ: Stupp (RT 60 Gy/30 fractions (fx)+TMZ) versus mini-Stupp (RT 40.05 Gy/15 fx+TMZ) and 2 regimens of RT without TMZ: 40 Gy/15 fx versus 25 Gy/5 fx. Methods: All GBM patients, 65-70 years, undergoing RT from 1 January 2014 to 31 December 2020 were retrieved and retrospectively evaluated. Patients were divided into 4 groups: group 1 was Stupp; group 2 was mini-Stupp; group 3 was 40,05 Gy/15 fx without TMZ; and group4 was 25 Gy/5 fx without TMZ. Results: Sixty patients were retrieved with median follow up of 12 months. In the analysis of groups 1 and 2, all variables were comparable (0.21<p<0.6). Median OS was 18 and 15 months, respectively, with no statistically significant difference (p=0.13). The OS at 2 years was 26% and 21% respectively, decreasing to 13% and 0% at 3 years. Analyzing groups 3 and 4, all variables were comparable (0.06<p<0.88). OS had no difference (p=0.5) with 7 months of median OS for both groups. Conclusions: From 65-70 years, if CHT is not viable, the 25 Gy/5 fx should be the standard. When CHT is possible, mini-Stupp appears to be equivalent to Stupp.